Effects of Volatile Anaesthetics and Iron Dextran on Chronic Inflammation and Antioxidant Defense System in Rats - Dyana Odeh; Nada Oršolić; Emanuela Adrović; Lydia Gaćina; Petra Perić; Sahar Odeh; Vedran Balta; Nikola Lesar; Marina Kukolj (MDPI AG, 2022)
Iron, as an essential microelement, is involved in cell proliferation, metabolism, and differentiation. It also modulates the fate and function of macrophages in hematopoiesis and macrophage-mediated inflammatory responses. On the other hand, anesthetics can affect the inflammatory process by modulating the response to stress or the functions of immune cells. The aim of this paper is to understand how excessive iron intake alters physiological, functional characteristics of peripheral tissues and whether different anesthetics can alter cell metabolism regarding oxidative stress (OS) and inflammation through regulation of macrophage polarization. Y59 rats were injected intraperitoneally with iron dextran solution at a dose of 50 mg/kg or were exposed to inhaled anesthetics sevoflurane and isoflurane and their combination for 28 days every other day. The results show that the use of anesthetics reduces the rat's organ weight and increases OS in peripheral tissues, leading to M1 macrophage polarization. Excessive iron intake leads to increased OS, inflammation, and an increased ratio of IL-12/IL-10 cytokines to the M1 macrophage phenotype. Iron, in combination with sevoflurane, has a protective effect in tissues showing the M2 phenotype of macrophages. The combination of iron dextran and isoflurane in rats leads to an increase in the erythropoiesis process made possible through the induction of hypoxia.